Civil Liability Provisions of the Notary Public(A comparative study) - Abdul Haleem Ibrahim, Researcher. Ibrahim; Ressan Jadder, Prof. Dr. Ghani (Basra studies journal, 2024)
The breach by the notary of any obligations imposed on him leads to his civil accountability when the elements of tort responsibility for his fault are available. Accordingly, we will be in front of the possibility of claiming the notary by the aggrieved party to compensate him for the damage he suffered. However, there must be a lawsuit filed before the competent court to claim compensation for the damage suffered by the aggrieved party as a result of the notary’s breach of one of his obligations. The civil liability lawsuit is the main effect resulting from the breach of the notary, and therefore the aggrieved party must follow specific procedures for the purpose of reaching his right, starting with the knowledge of the court competent to consider the case and the necessity of litigation against the defendant, as the lawsuit cannot be instituted without the availability of its parties, the plaintiff. And the defendant, and for this, the plaintiff must use the legal methods to prove his claim. If he fails to prove the notary public (the defendant) is able to pay that lawsuit, he does not have any right to compensation. Hence, if the notary public’s mistake and damage and the causal relationship between his mistake and the damage sustained by the aggrieved party are proven, we will be in front of determining the resulting penalties accordingly, starting from the compensation that the aggrieved party deserves to the liability and insurance agreements from them, and this is what we will show in this research.